Comprehensive Strategies for Enhancing Academic Achievement Among Underachieving School Students - Finorita, Eny Tantia; Mamun, Saepul; Suryaman, Maman; Wahyudin, Undang (LifeSciFi, 2025)
Underachievement among secondary school students remains a significant challenge. The mismatch between students’ academic potential and actual performance is driven by interconnected internal factors, such as low motivation and ineffective learning strategies, and external influences including parenting style, peer interactions, and academic pressure. This study aims to identify the factors contributing to underachievement, evaluate school-based intervention strategies, and analyze their effectiveness in improving motivation, learning behavior, and academic performance. Using a qualitative descriptive approach with a case study design, data were collected through in-depth interviews, classroom observations, and analysis of academic documents involving underachieving students, school counselors, subject teachers, and parents. The results indicate that interventions such as individual counseling, group guidance, learning development services, remedial programs, and collaboration between counselors and teachers provide positive improvements, yet their success depends heavily on intervention consistency, parental involvement, and students’ readiness to change. Integrated and continuous support is shown to enhance motivation and academic performance, though challenges persist related to family communication and commitment. The study emphasizes the need for comprehensive collaborative intervention models to more effectively address underachievement and support student academic success in secondary schools.